Bibliometric Study of CSIR-Institute of Himalayan Bioresource Technology (CSIR-IHBT) during 1990–2019 - Garg, K. C.; Kumar, S.; Kinwar, Deobardhan (Journal of Information and Knowledge, 2020)
The study examines the pattern of growth of papers published by CSIR-Institute of Himalayan Bioresource Technology (IHBT) during 1990-2019; identifies most prolific authors and their citation impact, communication pattern of scientists in terms of journal publishing country and impact factor of these journals as well as the pattern of domestic and international collaboration. Analysis of data indicates a consistent growth of output during the study period except a decline in 2019-2020. Publications appeared in journals published from the advanced countries of the West and more than half of the papers were published in medium, high and very high impact factor journals. The output is highly scattered in terms of journal publication as one-third of the papers were published in 28 journals. Only about 8% papers remained uncited and rest were cited one or more times. Of the 20 highly cited papers, six women scientists acted as first author. The study found that more than half of the papers were published in domestic and international collaboration. USA was the most collaborating country and academic institutions were found to be most domestic collaborating institutions in India as well as abroad. Among all the Indian institutions, Guru Nanak Dev University (Amritsar) was most collaborating domestic institution and University of Vienna, Austria from abroad.